PENYELIDIKAN KEJADIAN LUAR BIASA CAMPAK DI TK NUR JAMIL DESA CEMANI KECAMATAN GROGOL KABUPATEN SUKOHARJO PROPINSI JAWA TENGAH TAHUN 2011 - Wibowo Y; Rahayujati TB; Wisnuwijoyo AP (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2012)
Background: On Wednesday, July 27, 2011, District Health Office Sukoharjo received a report from the health center Sukoharjo Grogol that has been an increase in clinical cases of measles in NJ kindergarten in Cemani Village. To ascertain whether there has been an measles outbreak in kindergarten NJ, it is necessary to the investigation of the outbreak. Methods: Regional tracking outbreaks of measles cases is mainly done in kindergarten NJ, Cemani. Criteria and clinical measles cases is determinated by the diagnosis with laboratory tests and measles IgM positive cases in connection with the case of the epidemiology of measles IgM positive. This investigation is an observational analytic approach to the design of case-control study. Analytic form of univariate and bivariate test using 2x2 table so as to obtain the Odds Ratio (OR) and p-value. Results: Of the 37 clinical measles cases, 100% had fever, rash with cough/cold and 81.1% of cases with symptomps of conjunctivitis. Whole blood samples showed positive IgM measles, measles outbreaks proved to be a definite. Curve shape is propagated epidemic curve, showing the spread of measles disease from person to person directly. Most cases of infection in school (47.9%), hystory of household contact (26.8%), and neighbors/peer groups (23.9%). In the cases, 54.1% had no history of immunization against measles and 83.8% had no history of measles. In contrast to the controls, 91.1% had a history of measles immunization. Related variables are statistically significant are not immunized against measles with OR 13.3 (95% CI, 3.471 to 51.223, p = 0.000), did not get sick with Vitamine A before OR = 8.4 (95% CI, 1.728 to 40.883; p = 0.003) and no history of previous measles OR = 0.456 (95% CI, 0.352 to 0.591, p = 0.025). Conclusions: The outbreak that occured in NJ TK due to the confirmation of positive measles IgM measles. Attack Rate of both boys and girls in NJ highest in the age group 4 to 4.5 years (TK 0 small) are respectively 31.4% and 32.1%. Mode of transmission is mainly through contact with people at school. Risk factors for incidence of measles is not immunized and did not receive Vitamin A before illness.